2020
DOI: 10.1002/ccd.29063
|View full text |Cite
|
Sign up to set email alerts
|

Transcatheter aortic valve replacement in patients with severe comorbidities: A retrospective cohort study

Abstract: Objective To investigate the long‐term outcomes of patients with severe comorbidities (sCM) undergoing transcatheter aortic valve replacement (TAVR). Background The benefit of TAVR may be limited among patients with sCM due to a lack of mortality‐ or quality‐of‐life‐benefit. Methods All TAVR patients in the Allina Health System between January 1, 2011 and August 7, 2018 were included (n = 890, 82 ± 8 years, 55% men). sCM included: severe lung disease, severe liver disease, end‐stage renal disease, severe, seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 47 publications
1
0
0
Order By: Relevance
“…Elderly patients benefit from this procedure mainly due to reduced complications compared to SAVR, multiple coexisting comorbidities, and their frail state. Findings from our study showed that the mean age from STEROID and NOSTEROID groups was over 78 years, consistent with other studies that revealed that TAVR is often carried out in elderly patients [11][12][13][14][15]. The use of chronic corticosteroid therapy is not uncommon in this set of patients due to the presence of comorbidities (e.g., rheumatoid arthritis, interstitial pneumonia, autoimmune hepatitis, polymyalgia rheumatica, systemic lupus erythematosus, multiple myositis, scleroderma) [6] which requires the use of this medication.…”
Section: Discussionsupporting
confidence: 91%
“…Elderly patients benefit from this procedure mainly due to reduced complications compared to SAVR, multiple coexisting comorbidities, and their frail state. Findings from our study showed that the mean age from STEROID and NOSTEROID groups was over 78 years, consistent with other studies that revealed that TAVR is often carried out in elderly patients [11][12][13][14][15]. The use of chronic corticosteroid therapy is not uncommon in this set of patients due to the presence of comorbidities (e.g., rheumatoid arthritis, interstitial pneumonia, autoimmune hepatitis, polymyalgia rheumatica, systemic lupus erythematosus, multiple myositis, scleroderma) [6] which requires the use of this medication.…”
Section: Discussionsupporting
confidence: 91%